Perception towards the preparedness for disaster management among nurses in community clinics / Fatimah Sham …[et al.] - Sham, Fatimah; Musa, Lailatul Hazzliza; Mohamed, Nor Marini; Othman, Norjah (Universiti Teknologi MARA Shah Alam, 2018)
Disasters are defined as extraordinary events which occur abruptly, bringing great damage or harm, loss, and destruction to people and the environment. Nurses may have a more conflict and difficulties in disaster decision making where the victim condition need to be treated in disaster place. Nurses play a key role in hospital as a leaders and managers in the disaster operation and command center but limited data shows that the nurses experience in disaster management. The aim of this study is to evaluate the perception of knowledge and skills on the preparedness in disaster management among nurses in community clinics. A descriptive cross-sectional study was conducted in 27 government clinics in one of the states in Malaysia with a convenient sampling, 260 participants are selected. The questionnaire consisted of three sections; socio-demographic characteristics, the perception of knowledge and skill towards preparedness for disaster management rated on a Likert scale. In the effort to collect the intended data, a self-report questionnaire adapted and modified from Disaster Preparedness Evaluation Tool (DPET) was implemented (Alrazeeni, 2015). This study revealed that Nurses in these community clinics were moderate in terms of the perception of knowledge (Mean= 3.65, SD= 0.61) and the perceived skills (Mean= 3.68, SD= 0.56) on the preparedness in Disaster Management. Nevertheless, they were interested in disaster preparedness management training (n=227, 87.3%) and were confident as first responders of disaster (Mean= 3.88, SD= 0.61). However, they were not much involved in disaster preparedness plan (Mean= 3.23, SD= 0.90) and claimed that there was a lack of leadership figure in disaster situation (Mean= 3.06, SD= 0.92). In conclusion, nurses in community clinics need to gain knowledge and skills by involving themselves in disaster planning and drills as the preparation for disaster management for them to be the first responders in helping and managing people in this situation.